Preliminary Studies on the Epidemiology of the Potato Aphids in West Bengal (Homoptera: Aphididae). - Banerjee, S. N.; Basu, A. N. (Contributions to Entomology = Beiträge zur Entomologie, 1956)
M. persicae and A. gossypii are the two species of aphids which infest potato crop in West Bengal. Both the species are highly polyphagous and have a wide range of host plants. They infest the potato crop at the early stage of development and persist almost throughout the growing season of the crop. Potato fields nearabout Calcutta are therefore, subjected to the attack of the aphids throughout the growing season. Both the species are abundant before the sowing of potato, in areas near Calcutta. Early sowing of potato in these areas, therefore, is not likely to be effective in avoiding their infestations. The production of the alatae and the peak period of infestation seem to be largely dependant on the condition of the foliage. The aphids are not uniformly distributed on the potato foliage. They are particularly abundant on the middle and lower leaves and as such, insecticidal sprayings should adequately cover the entire foliage for satisfactory control of the aphids.